All-trans-retinoic acid activates the pro-invasive Src-YAP-Interleukin 6 axis in triple-negative MDA-MB-231 breast cancer cells while cerivastatin reverses this action - Belén Mezquita (Nature Portfolio, 2018)
Abstract All-trans-retinoic acid (RA), the active metabolite of vitamin A, can reduce the malignant phenotype in some types of cancer and paradoxically also can promote cancer growth and invasion in others. For instance, it has been reported that RA induces tumor suppression in tumor xenografts of MDA-MB-468 breast cancer cells while increasing tumor growth and metastases in xenografts of MDA-MB-231 breast cancer cells. The signaling pathways involved in the pro-invasive action of retinoic acid remain mostly unknown. We show here that RA activates the pro-invasive axis Src-YAP-Interleukin 6 (Src-YAP-IL6) in triple negative MDA-MB-231 breast cancer cells, yielding to increased invasion of these cells. On the contrary, RA inhibits the Src-YAP-IL6 axis of triple-negative MDA-MB-468 cells, which results in decreased invasion phenotype. In both types of cells, inhibition of the Src-YAP-IL6 axis by the Src inhibitor PP2 drastically reduces migration and invasion. Src inhibition also downregulates the expression of a pro-invasive isoform of VEGFR1 in MDA-MB-231 breast cancer cells. Furthermore, interference of YAP nuclear translocation using the statin cerivastatin reverses the upregulation of Interleukin 6 (IL-6) and the pro-invasive effect of RA on MDA-MB-231 breast cancer cells and also decreases invasion and viability of MDA-MB-468 breast cancer cells. These results altogether suggest that RA induces pro-invasive or anti-invasive actions in two triple-negative breast cancer cell lines due to its ability to activate or inhibit the Src-YAP-IL6 axis in different cancer cells. The pro-invasive effect of RA can be reversed by the statin cerivastatin.